HUBUNGAN ANTARA KEPERCAYAAN DIRI SISWA DENGAN KETERAMPILAN BERBICARA BAHASA INGGRIS SISWA KELAS V SDN PERUMNAS 1 KOTA TANGERANG - Julya Fatharani; Asih Rosnaningsih; Ina Magdalena (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study is to answer the problem of how the relationship between self-confidence and the ability to speak English in elementary school students. This research took place in class V SDN Perumnas 1 Tangerang City. This study used a quantitative approach using a survey research method used through the SPSS statistical test. The population in this study were all fifth grade students at SDN Perumnas 1 Kota Tangerang, totaling 45 students. The sample used was 30 students with the sampling technique used was Simple Random Sampling. The results of this study indicate that there is a relationship between students' self-confidence and their ability to speak English. The results of statistical analysis using the product moment correlation formula show that the value of rcount is equal to 0.478 and rtable at a significant level of 0.05 is 0.301, so rcount<rtable. This shows that students' self-confidence is one of the components that determines the mastery of speaking English. Keywords: Confidence, Speaking Skills, English.